Tajdid Dan Transformasi Pendidikan Islam Di Era Revolusi Industri 4.0 - Indriana Try Meliwatdani; Asnia, Asnia; St. Nurhayati Ali; Muhammad Nur Maallah (Journal of Humanities, Social Sciences, and Education, 2026)
The development of the Industrial Revolution 4.0 has brought about major changes in various sectors of life, including education. Islamic education, as a system based on Islamic values, is required to be able to adapt dynamically without losing its normative identity. This article aims to examine the concept of tajdid (renewal) and the transformation of Islamic education in responding to the challenges of the digital era through a literature study approach. The method used is a literature review of scientific articles, books, and research reports relevant to the themes of Islamic education, tajdid, and the Industrial Revolution 4.0. The results of the study indicate that Islamic education faces serious challenges in the form of technological disruption, changes in the character of digital generation students, and the demands of 21st-century competencies that emphasize creativity, critical thinking, collaboration, and digital literacy. In this context, tajdid is understood as a contextual and progressive renewal effort without abandoning the basic principles of Islamic teachings. The transformation of Islamic education is reflected in changes to the curriculum, learning methods, the role of educators, and the use of digital technology as a medium and learning resource. The integration of Islamic values ​​with digital technology is key to ensuring that the educational process not only produces individuals who are intellectually and technologically proficient but also possess Islamic character. The conclusion of this article emphasizes that the renewal and transformation of Islamic education are strategic imperatives to address the challenges of the Industrial Revolution 4.0 while maintaining the primary mission of Islamic education to develop individuals of faith, knowledge, and noble character.